The Effect Of Self-Efficiency On Public Speaking Anxiety In Students Of The Faculty Of Education At University “X” - Dinda Kristina Hari Wardani; Awang Setiawan Wicaksono; Noer Suci Endah (Universitas Muhammadiyah Banjarmasin, 2023)
Anxiety in public speaking is a problem that is often encountered, especially in students, excessive anxiety can affect individual performance or academic life. So that it takes confidence in individuals about their ability to deal with various situations and conditions which are commonly called self-efficacy because it is thought to affect anxiety when appearing in public. This study aims to determine the effect of self-efficacy on public speaking anxiety in students of the Faculty of Education, University of Muhammadiyah Gresik. This research method is quantitative by using incidental sampling and the number of respondents is 164 people. The results of the analysis using simple regression with the SPSS application obtained a sig value of 0.000, meaning that the significant value is smaller <0.05. Based on the results of the SPSS, it is known that the R square is 0.409 which means that the public speaking anxiety variable contributes 16% to the self-efficacy variable. While the remaining 84% is influenced by other variables not examined. Suggestions in this study Education students should be able to rely on their abilities and be more calm when facing difficulties.